Influence of high temperatures on Post-COVID-19 conditions - D Hristova; I Simova; T Vekov (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Patients with chronic diseases are especially vulnerable on hot days because high temperatures lead to exacerbation of a number of cardiovascular, neurological, autoimmune, and other chronic diseases. Acute SARS-CoV-2 infection has left tens of thousands of Bulgarians suffering from a new chronic disease: Post COVID-19 syndrome. The Bulgarian Cardiac Institute, in trend with innovations, has launched the first worldwide study to establish the relationship between high ambient temperatures and Post COVID-19 conditions. It covers 1310 citizens and was held during the hottest month in history - July 2021. Eight districts in Bulgaria are covered, and for each of them, we calculated a number of meteorological parameters and determined their influence on the persistent signs and symptoms. Shumen District is the district with the highest percentage of citizens with peristaltic complaints (86%) and the most pronounced in terms of severity. This is the area with the lowest average daily maximum temperature (28.44º), the highest average night minimum temperature (20.42º), and the lowest average temperature amplitude (8.02º) for July 2021. It is characteristic that the neurological symptoms (dizziness, headache, impaired concentration, and memory) are predominant at a lower temperature amplitude (Shumen district). Symptoms of the cardiovascular system (shortness of breath, fatigue, palpitations, chest pain) are more commonly reported at higher temperature amplitudes (Pleven district). The results of the study show that high values ​​of ambient temperatures affect Post COVID-19 conditions. The most unfavorable effect is exerted by the high average night minimum temperatures and the small temperature amplitude. Cardiovascular symptoms are particularly pronounced at large temperature amplitudes and neurological at small temperature amplitudes. Post-COVID-19 conditions are unpredictable and patient care continues during the hot months.